Greetings in Africa – Beyond the handshake: An essay on greeting and leave-taking rituals as communication practice in Sub-Saharan African agrarian societies - Schiefer, U.; Carvalho, A. L.; Nascimento, A. C. (Kwanissa: Revista de Estudos Africanos e Afro-Brasileiros, 2021)
In African Agrarian Societies greeting and leave-taking rituals are an essential part of the communication processes that constitute these societies as collective entities. Through elaborate forms of greeting and leave-taking people initiate and end communication and interaction processes within a framework of collective identities and cultures. Intricate greeting rituals allow to deal with all forms of encounters, with living people as well as with the spirits of the deceased. Greeting rituals are acquired through lengthy periods of learning. Their mastery is the sign of being an adult and competent member of society. External actors from different cultures often seem to be unaware of the subtleties of these greeting rituals. They ignore them at a cost. This essay provides some insights into the inner workings of African societies concerning the framing of most of their internal and external communication processes that are as vital for their lifeworlds as they are for their interaction with external actors from different spheres. Analysing the societies in a comprehensive manner as self-organising entities within an ethnic matrix clearly shows the limits of reducing greeting rituals to mere speech acts between individuals and proves that some of the fundamental assumptions of modern communication theories are not valid for African Agrarian Societies.